(untitled) (مجلة إحالات, 2026)
Boujloud Spectacle is considered one of the most performing, popular and ritual scene Moroccan. The show is practiced after the celebration of Eid al-Adha in particular settings. It is subject to specific rites and is performed according to the usual conditions of the official theatre. It contains extraordinary mythological significances and combines what is sacred with what is profane. I opened this study with a preface in which I highlighted the importance of theatre. I divided it into two elements. The first one described the show and the second one analyzed it on the theatrical and mythic levels. I closed the study with a conclusion which showed that it was an extraordinary scene where the contradictions of the sacred and the profane are adjacent. I used the morphological method and the mythological metod.